Effect of Fluorescent Condensation Plates (CaWO4) on Radiation Dose Received at X-Ray. - Qusay Aldulayme; Muhsin Albadrane (College of Education for Pure Sciences, 2009)
Abstract The present study aims to investigate the effect of using (CaWO4) as intensifying screen on radiation dose received by patients exposed to dental investigation by x-ray. It was found that intensifying screen increases, the radiation dose from )4-6( times according to the properties of the intensifying materials used. The optical density of the x-ray film was measured by using densitometer. According to our measurements, a decrease in radiation dose was approximately 24% for the same condition .Am241 was used because its energy (59.5keV) is close to the energy of x-ray in dental radiography.